2023
DOI: 10.1002/cae.22690
|View full text |Cite
|
Sign up to set email alerts
|

Advanced learning methods in maritime education and training: A bibliometric analysis on the digitalization of education and modern trends

Taha Talip Türkistanli

Abstract: The minimum requirements in maritime education and training (MET) are set by the International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW). First established in 1978, the STCW convention standardized educational procedures for seafarers. Since then, it has become the most influential regulatory document for maritime education. The STCW code had major revisions in 1995 and 2010. These amendments were in response to the recognized need to bring the Convention up to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 156 publications
0
4
0
Order By: Relevance
“…Maritime Education and Training in the context of digitalization and training methods and tools applied for the training of maritime human resources attract the increased interest of the research community. Turkistanli (2023) conducted bibliometric research on the digitalization of education and modern trends and found an increase in interest in learning tools and models in Maritime Education and Training with publications and citations growing impetuously after 2017. Human factor issues are found to be a dominant narrative, with the emphasis on the improvement of nontechnical skills.…”
Section: Future Skills and Automation In The Maritime Industrymentioning
confidence: 99%
“…Maritime Education and Training in the context of digitalization and training methods and tools applied for the training of maritime human resources attract the increased interest of the research community. Turkistanli (2023) conducted bibliometric research on the digitalization of education and modern trends and found an increase in interest in learning tools and models in Maritime Education and Training with publications and citations growing impetuously after 2017. Human factor issues are found to be a dominant narrative, with the emphasis on the improvement of nontechnical skills.…”
Section: Future Skills and Automation In The Maritime Industrymentioning
confidence: 99%
“…The Tuerkistanli review study [30] conducted an in-depth review and bibliometric analysis of the advanced teaching methods in the field of MET and showed a steady increase in publications, especially under the influence of regulatory bodies such as the IMO and STCW. The challenges in disseminating different perspectives within research on advanced teaching methods in MET highlight the need for regulatory changes to accommodate innovative approaches, especially in response to disruptive events such as the COVID-19 pandemic.…”
Section: Maritime Law and Review Studiesmentioning
confidence: 99%
“…In the last decade, we have seen the rise of studies that are focused on the latter, to study simulator-based maritime training through ethnographic studies in the tradition of EMCA (e.g., Sellberg, 2018), socio-cultural perspectives (e.g., Hontvedt & Arnseth, 2013;Wahl, 2020) or distributed cognition (Sellberg, 2017). What these studies have in common is that they take place within a small cluster of researchers in Sweden and Norway using video recorded simulation activities as the basis for doing close and detailed interaction analyses of navigation training (Türkistanli, 2023). This review builds heavily on those studies to outline social and pedagogical aspects of importance for informing design of an ILS intended to be used in navigation training in full-mission bridge simulators.…”
Section: Ethnographies Of Simulator-based Maritime Trainingmentioning
confidence: 99%